Germline variation of Ribonuclease H2 genes in ovarian cancer patients - Rahel Polaczek; Peter Schürmann; Lisa-Marie Speith; Robert Geffers; Matthias Dürst; Peter Hillemanns; Tjoung-Wo; Clemens Liebrich; Thilo Dörk (BMC, 2020)
Abstract Epithelial ovarian carcinoma (EOC) is a genetically heterogeneous disease that is partly driven by molecular defects in mismatch repair (MMR) or homology-directed DNA repair (HDR). Ribonuclease H2 serves to remove mis-incorporated ribonucleotides from DNA which alleviates HDR mechanisms and guides the MMR machinery. Although Ribonuclease H2 has been implicated in cancer, the role of germline variants for ovarian cancer is unknown. In the present case-control study, we sequenced the coding and flanking untranslated regions of the RNASEH2A, RNASEH2B and RNASEH2C genes, encoding all three subunits of Ribonuclease H2, in a total of 602 German patients with EOC and of 940 healthy females from the same population. We identified one patient with a truncating variant in RNASEH2B, p.C44X, resulting in a premature stop codon. This patient had high-grade serous EOC with an 8 years survival after platinum/taxane-based therapy. Subsequent analysis of TCGA data similarly showed a significantly longer progression-free survival in ovarian cancer patients with low RNASEH2B or RNASEH2C expression levels. In conclusion, loss-of-function variants in Ribonuclease H2 genes are not common predisposing factors in ovarian cancer but the possibility that they modulate therapeutic platinum response deserves further investigation.